TIMI (Thrombolysis in Myocardial Infraction) flow grade in ST Elevation Myocardial Infarction after Primary Percutaneous Intervention - Tamrakar, Rikesh; Rajbhandari, Rajib; KC, Sanjay Singh (Europasian Journal of Medical Sciences, 2021)
Background: Timely reperfusion, preferably by primary percutaneous intervention (PCI) has been the guiding principle for the treatment of patients with acute ST-elevation myocardial infarction (STEMI). TIMI flow grade of the culprit lesion after the procedure has shown to have the significant implication in clinical outcome. Objective: We aimed to study the relation of TIMI flow grade with the hospital outcome and complication among patients of STEMI. Methods: All consecutive acute STEMI patients undergoing primary PCI during the study period (January 2020 to June 2020) were analyzed for correlation between TIMI flow grade and clinical outcome during the hospital stay. Prior approval was taken from the institutional review board. The study design was a retrospective observational study. Result: 51(55%) patients had achieved the TIMI 3 flow after the primary PCI. The number of patients achieving TIMI flow of 2,1 and 0 after the procedure was 34(37%), 6(6.5%), and 2(2%). Incidence of traditional risk factors like dyslipidemia, diabetes, hypertension was higher in TIMI flow <2. TIMI flow <2 was also associated with more adverse events namely cardiogenic shock, arrhythmias, in-hospital mortality, and overall major adverse cardiovascular events. Conclusion: Patients with dyslipidemia had poor TIMI flow grades during primary PCI. Similarly, patients having hypertension, diabetes mellitus, and late presentation showed a tendency for TIMI flow <2. Also, the poor TIMI flow grade after primary PCI had unfavorable clinical outcomes like increased complications and mortality.